Effect of Motor Relearning Program with Obstacle Walking on Dynamic Gait Performance and Functional Mobility in Subacute Stroke Subjects. - Patra, Mainak; Kunduru, Sudheera (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Gait difficulties are common post-stroke due to muscle weakness and postural imbalance. Motor relearning program is known to improve motor skills through task oriented practice, appropriate feedback and active participation of subjects. Obstacle walking helps in improving gait parameters, stepping over objects, walking endurance and reduces fall risk. Objectives: To determine effect of Motor Relearning Program with obstacle walking on dynamic gait performance and functional mobility in sub-acute stroke subjects. Materials and Methods: 30 sub-acute stroke subjects were assigned to one of the two groups. Group-A received Motor Relearning Program and Group-B received Motor Relearning Program with obstacle walking for 30 minutes, 5 days a week for 4 weeks. Both groups received 15 minutes of conventional exercises for upper limb. Dynamic gait performance and functional mobility were assessed pre- and post-intervention at 4 weeks using Dynamic Gait Index and Motor Assessment Scale. Results: Pre-test scores of DGI and MAS were 11.53±3.53 and 3.83±0.48 in Group-A, 12.43±4.12 and 3.67±0.81 in Group-B which improved to 15.80±3.82 and 4.07±0.59 in Group-A, 18.67±4.86 and 4.73±0.96 in Group-B, post-intervention. Within group comparison of pre to post-test scores of DGI and MAS was found to be statistically significant in both groups. When post-test scores of DGI and MAS were compared in between groups, Group-B was found to be statistically significant than Group-A (p<0.05). Conclusion: Both interventions were individually effective but Motor Relearning Program with obstacle walking was better than Motor Relearning Program alone to improve dynamic gait performance and functional mobility in sub-acute stroke subjects.